calcule a raiz quadrada de 36 mais raiz quadrada de 49 menos raiz quadrada de 1
![\sqrt{36 + \sqrt{49 - \sqrt{1 = } } } \sqrt{36 + \sqrt{49 - \sqrt{1 = } } }](https://tex.z-dn.net/?f=+%5Csqrt%7B36+%2B++%5Csqrt%7B49+-++%5Csqrt%7B1+%3D+%7D+%7D+%7D+)
Soluções para a tarefa
Respondido por
0
Explicação:
√36=6 pois 6×6=36
√49=7 pois 7×7=49
√1=1 pois 1×1= 1
6+7+1=14
Resposta:
14
Perguntas interessantes
ENEM,
10 meses atrás
ENEM,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás